Keputusan Konsumen Dalam Pembelian Virtual Items pada Game Online Mobile Legends: Bang Bang - Fadhilah Diva Oktaviansyah; Ririn Puspita Tutiasri (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The online game Mobile Legends: Bang Bang is a free-to-play online game that is popular in various circles. In the game there are various interesting virtual items, both in terms of game mechanics and the design of the characters or available heroes. Various types of virtual items available in the game can attract players to top up and buy virtual items as needed and desired. This study uses a descriptive qualitative research method to find out the reasons for various aspects of the consumption value of the players in making top ups to buy virtual items in the game. The results of this study indicate that decorative props such as those with attractive designs are the main reason for players to top up in the game, as well as the gameplay of the character they like is another reason for buying skins. Apart from that, satisfaction and support from family to be able to work in e-sports is also one of the reasons for players in playing the online game Mobile Legends: Bang Bang to keep topping up. Keywords: The Consumption Value, Online Game, Mobile Legends: Bang Bang